2004
DOI: 10.1093/jhered/esi018
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Chromosomal Localization of rDNA Sites in “Safed Musli” Chlorophytum Ker-Gawl and Their Physical Measurement by Fiber FISH

Abstract: Fluorescence In Situ Hybridization (FISH) technique has been applied on somatic chromosomes and extended DNA fibers in the medicinally important species of Chlorophytum to elucidate physical localization and measurement of the rDNA sites using two rRNA multigene families homologous to 45S and 5S rDNA. The two species of Chlorophytum, namely C. borivillianum and C. comosum, both with 2n = 28, reveal diversity for copy number and localization of rDNA sites. C. borivillianum is comprised of five 45S-rDNA sites:on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 25 publications
1
13
0
1
Order By: Relevance
“…congensis seems to be absent or not detected in C. arabica. The loss of rDNA locus in allotetraploid species, compared with their progenitors, has already been documented (Hanson et al 1996;Comai et al 2000;Krishnan et al 2001;Liu et al 2003;Lavania et al 2005). For Mishima et al (2002), 5S sites are often eliminated after polyploidization, while 18S sites seem to be more conserved.…”
Section: Allotetraploid Origin Of C Arabicamentioning
confidence: 94%
“…congensis seems to be absent or not detected in C. arabica. The loss of rDNA locus in allotetraploid species, compared with their progenitors, has already been documented (Hanson et al 1996;Comai et al 2000;Krishnan et al 2001;Liu et al 2003;Lavania et al 2005). For Mishima et al (2002), 5S sites are often eliminated after polyploidization, while 18S sites seem to be more conserved.…”
Section: Allotetraploid Origin Of C Arabicamentioning
confidence: 94%
“…They may be unlinked on the same chromosome arm, or located on different chromosomes, but variation in locus size/copy number is known to occur across genotypes and geographical regions (Tagashira et al 2009). Although the occurrence of 5S rDNA sites has been shown to be associated with nucleolus in soybean, common bean (Shi et al 1996) and wheat (Mukai et al 1991), the occurrence of two rDNA gene families on the same chromosome as observed in Chlorophytum (Lavania et al 2005) as well as here is unusual and may serve as a marker to aid chromosome identification. In the last two decades, FISH studies have been conducted in numerous plant species to elucidate the number and localization of rDNA sites.…”
Section: Linear Chromosome Differentiationmentioning
confidence: 59%
“…The detection of FISH signals was done according to Lavania et al (2005) by incubating the slides for 1 h at 37 • C in the detection mix. The biotinylated 45S DNA probe was detected by avidin DN conjugated with Cy3 (0.025% v/v), and digoxigenin-labelled DNA was detected by anti-digoxigenin (Fab fragment) conjugated with FITC (fluorescein isothiocynate, 1%) in 5% (w/v) BSA (borine serum albumin).…”
Section: Probe Labelling and Fluorescence In Situ Hybridizationmentioning
confidence: 99%
“…Four millimeter long shoot buds encapsulated in 3.0%sodium alginate matrix polymerized by 100mM solution of CaCl 2 .2H 2 O yielded best results. Recently, Fluorescence In Situ Hybridization (FISH) technique has been applied on somatic chromosomes and extended DNA fibers in the medicinally important species of Chlorophytum to elucidate physical localization and measurement of the rDNA sites using two rRNA multigene families homologous to 45S and 5S rDNA [47].…”
Section: Safed Musli Chlorophytum Borivilianummentioning
confidence: 99%